2018
DOI: 10.24017/science.2018.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Determination the site of antibiotic resistance genes in Escherichia coli isolated From Urinary Tract Infection

Abstract: This study includes isolation of 25 isolates of Escherichia coli (E. coli  ) strain from urinary tract samples in a pregnant woman. Microbiological and biochemical tests were used to identify the resistant bacteria of this genus. Screening methods were used to determine bacterial isolates for their resistance to 10 antibiotics include: Amikacin (Ak), Amoxicillin (Ax), Ampicillin (Ap), Chloramphenicol (Cm), Ciprofloxacin (Cip), Erythromycin (Er), Nalidixic acid (Nal), Penicillin (Pen), Tetracycline (Tet) and Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This study found that tetracycline and chloramphenicol resistance was each at 46.6%, whereas (Mohammed, 2018) in Iraq found that the same antibiotics were each resistant to 88%, and (Abdel Hamid and Abozahra, 2017) in Egypt found that tetracycline resistance was 64.3% by E. coli. This might be because the bacteria altered the permeability of its outer membrane and had efflux pumps.…”
Section: Antibioticmentioning
confidence: 78%
“…This study found that tetracycline and chloramphenicol resistance was each at 46.6%, whereas (Mohammed, 2018) in Iraq found that the same antibiotics were each resistant to 88%, and (Abdel Hamid and Abozahra, 2017) in Egypt found that tetracycline resistance was 64.3% by E. coli. This might be because the bacteria altered the permeability of its outer membrane and had efflux pumps.…”
Section: Antibioticmentioning
confidence: 78%
“…While (100%) were sensitive to imipenem and meropenem 19 . Another study in Iraq in Erbil 2018 included 25 isolates of UPEC, resistance percentage between 28 to 96 % to amikacin, amoxicillin, ampicillin, chloramphenicol, ciprofloxacin, erythromycin, nalidixic acid, penicillin, tetracycline, and trimethoprim 20 . A study in Iran in 2018 included 60 strains of uropathicE.coli was investigated antibiotic susceptibility using the Kirby Bauer disk diffusion method.…”
Section: Antibiotic Susceptibilitymentioning
confidence: 99%